Association between elevated glycosylated hemoglobin levels and hypertension among US adults: NHANES 2011–2018 - Beibei Luo; Wenbo Xu; Feng Luo; Shuqiong Zhang; Xiaofei Li (BMC Cardiovascular Disorders)
Abstract Introduction Hypertension (HTN) and diabetes frequently coexist. This study aims to elucidate the associations between HTN and glycosylated hemoglobin (HbA1c), as well as the connections between distinct forms of HTN and HbA1c. Methods We collected data from National Health and Nutrition Examination Survey (NHANES) 2011–2018 in this study, including anthropometric tests and biochemical measures. The HbA1c levels were grouped by participants with diabetes, prediabetes, or no diabetes. Correlations between HbA1c and HTN, isolated systolic hypertension (ISH), and isolated diastolic hypertension (IDH) risk were investigated by logistic analyses. A fitting curve has drown to describe the association between HTN and HbA1c. Results Among the 10,503 enrolled participants, The prevalence of HTN notably increased with higher HbA1c levels (P < 0.001). In the adjusted model, compared to the lowest HbA1c group, the odds ratio (OR) with its 95% confidence interval (CI) was 1.22 (1.07 ~ 1.39) for the highest HbA1c group. There was a significant increase in the risk of ISH with higher HbA1c levels in group 3 compared to group 1 (OR: 1.3, 95% CI: 1.1 ~ 1.53).The adjusted model revealed no significant association between HbA1c levels and the risk of IDH. Conclusion There is a independent influence of HbA1c on HTN risk in adults in the United States. Notably, the risk of developing HTN increases most rapidly when HbA1c levels approach 5.5%.